2000
DOI: 10.1590/s1516-31802000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the p53 gene by PCR-SSCP in ten cases of Wilms’ tumor

Abstract: Evaluations of exons 5-9 of the p53 gene in DNA samples extracted by PCR-SSCP from 10 Wilms' tumors in children at different stages, and DNA sequencing. Changes in SSCP analy-sis were observed in exon 8 in two samples. The probable muta-tions were not confirmed by DNA sequencing. The absence of point mutations in p53 gene observed in the 10 samples of Wilms' tumor studied agrees with literature data, with DNA sequencing being of fundamental importance for the confirmation of possible mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Mutations in WT1 or epigenetic defects on chromosome 11p15 contribute to the major genetic susceptibility locus [ 8 ]. Previous studies have reported several non-WT1 loci with smaller effects on the genetic predisposition for WT, including p53 gene [ 9 ], insulin-like growth factor-II gene [ 10 ], CTNNB1 gene [ 11 ], and H19 [ 12 ]. However, less than half of WT cases are attributable to known genes that are associated with WT risk; therefore, the exact pathogenesis of most WT cases remains unknown and identification of novel genetic loci is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in WT1 or epigenetic defects on chromosome 11p15 contribute to the major genetic susceptibility locus [ 8 ]. Previous studies have reported several non-WT1 loci with smaller effects on the genetic predisposition for WT, including p53 gene [ 9 ], insulin-like growth factor-II gene [ 10 ], CTNNB1 gene [ 11 ], and H19 [ 12 ]. However, less than half of WT cases are attributable to known genes that are associated with WT risk; therefore, the exact pathogenesis of most WT cases remains unknown and identification of novel genetic loci is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…A detecção do TP53 mutante pode ser feita pela análise molecular (detecção da seqüência de DNA) ou por estudos imunoistoquímicos, técnica que permite avaliar a expressão do gene TP53 através da proteína p53 presente na célula (Malkin et al, 1994;Cheah et al, 1996;Lahoti et al, 1996;Kusafuka et al, 1997;Govender et al, 1998;Defavery et al, 2000 (Cheah et al, 1996;Lahoti et al, 1996;Kusafuka et al, 1997;Govender et al, 1998;Beniers et al, 2001;Hill et al, 2003;Peres et al, 2004).…”
Section: A) Gene Tp53unclassified